Survei Kemampuan Renang Gaya Dada 30 Meter Pada Mahasiswa Olahraga Angkatan 2020 STKIP Kie Raha Kota Ternate - Rifaid Saiman; Rifan Ngaji (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to determine the level of ability in swimming the 30-meter breaststroke in sports students class of 2020 at STKIP Kie Raha, Ternate City. This research is a quantitative research with a survey approach. The sample in this study were 2020 STKIP Kie Raha Sports students, Ternate City, totaling 21 students. The results showed that: in the category "Very Good" by 9.523% (2 students), "Good" by 28.57% (6 students), "Medium" by 14.28% (3 students) "Less" by 47, 61% (10 students), and "Very Less" of (0 students). The conclusion of this study is that the level of ability in swimming the 30-meter breaststroke for sports students class of 2020 STKIP Kie Raha City of Ternate is in the "less" category with a percentage of 47.61% or there are 10 students